How does climate exacerbate root causes of livestock-related conflicts in Kenya? Climate Security Pathway Analysis - Sax, Niklas; Santa Cruz, Leonardo Medina; Carneiro, Bia; Liebig, Theresa Ines; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR FOCUS Climate Security, 2022)
This factsheet gives answers on how climate exacerbates root causes of livestock-related conflict in Kenya, using an impact pathway analysis. Three main impact pathways are identified: